Effects of germicidal far-UVC on ozone and particulate matter in a conference room - Farideh Hosseini Narouei; Zifeng Tang; Shiqi Ian Wang; Raabia H. Hashmi; David Welch; Sandhya Sethuraman; David J. Brenner; V. Faye McNeill (PLoS ONE, 2025)
The application of 222 nm light from KrCl excimer lamps (GUV222 or far-UVC) is a promising approach to reduce the indoor transmission of airborne pathogens, including the SARS-CoV-2 virus. GUV222 inactivates airborne pathogens and is believed to be relatively safe for human skin and eye exposure. However, UV light initiates photochemical reactions which may negatively impact indoor air quality. We conducted a series of experiments to assess the formation of ozone ( O 3 ), and resulting formation of secondary organic aerosols (SOA), induced by commercial far-UVC devices in an office environment (small conference room) with an air exchange rate of 1.3 h − 1 . We studied scenarios with a single far-UVC lamp, corresponding to the manufacturer’s recommendations for disinfection of a space that size, and with four far-UVC lamps, to test conditions of greater far-UVC fluence. The single lamp did not significantly impact O 3 or fine particulate matter levels in the room. Consistent with previous studies in the literature, the higher far-UVC fluences lead to increases in O 3 of 5 to 10 ppb above background, and minor increases in particulate matter (16% ± 10 % increase in particle number count). The use of far-UVC at minimum intensities required for disinfection, and in conjunction with adequate ventilation rates (e.g. ANSI/ASHRAE recommendations), may allow the reduction of airborne pathogen levels while minimizing the formation of air pollutants in furnished indoor environments.